Mialgias: Approaches to differential diagnosis, treatment - Nadezhda Aleksandrovna Shostak (Современная ревматология)
Differential diagnosis in muscle pains often presents great difficulties so all existing signs of the disease should be carefully considered to make its diagnosis and to prescribe adequate therapy. The paper considers the causes of muscle pains, laboratory and instrumental studies (immunological tests, determination of the level of specific muscular enzymes, primarily creatine phosphokinase – CPK, etc.), and the main reasons for enhanced plasma CPK activity. It also describes acute and chronic mialgias associated with enhanced plasma CPK activity, as well as diseases in which mialgias are related to the normal level of CPK, myofascial syndrome (MFS) and fibromyalgia (FM) in particular. The characteristic features of MFS are given in its diagnostic criteria. It is stated that a differential diagnosis should be made between MFS and major muscle pain-associated abnormalities, such as polymyalgia rheumatica, FM, etc. Diagnosticcriteria for polymyalgia rheumatica are given. A MFS treatment algorithm is presented. Local exposure methods applied to altered musculoligamentous structures in combination with myorelaxants and non-steroidal anti-inflammatory drugs assume paramount importance in MFS.